Molecular analysis of several in-house rRT-PCR protocols for SARS-CoV-2 detection in the context of genetic variability of the virus in Colombia (2023)
The COVID-19 pandemic caused by SARS-CoV-2 is a public health problem unprecedented in the recent historyof humanity. Different in-house real-time RT-PCR (rRT-PCR) methods for SARS-CoV-2 diagnosis and the ap-pearance of genomes with mutations in primer.